Casos y cosas: semanario popular (Vol. 2, No. 64) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Dictadura policial, Lo que yo he visto, Revelaciones políticas, Correo franco y con franqueza, Apuntes de un tonto, Buzón.

ENGLISH: Includes: Police dictatorship, What I have seen, Political revelations, Franco mail and with frankness, Notes of a fool, Mailbox.
Cases and things: popular weekly magazine (Vol. 2, No. 64)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas